Optimization of Fog Computing Efficiency by Decreasing the Latency Level in the Medical Environment - Al-Hagery , Mohammed Abdullah; Alharbi , Ameenah Mohammad (International Journal of Membrane Science and Technology, 2023)
Fog computing is the latest technique in today's cloud computing environment, with the advent of this technology. One of the most important parameters affecting fog computing performance is latency. Cloud computing was very effective but needed help in its efficiency according to the values of this parameter, mainly due to its distributed nature. With the advent of the "fog" technology, the big cloud was separated into many small cloudlets, where each cloudlet is a mobility-enhanced small scale. A new architectural element extends today's cloud computing infrastructure. The term "Cloudlets" combined to form fog Computing, which has the main advantages of improving its characteristics listed above. This paper aims to improve the efficiency of the cloud-computing environment by developing a simulation system to test the best structure before applying it in a real environment. This system will improve the efficiency based on the latency parameter to provide researchers and interested parties with a clear vision to improve the work in a simulation environment and achieve the same methodology in real environments. The simulation system was developed in such a way as to reduce the delay of tasks to increase the performance rate. The results of the simulation system are promising and can be applied in the medical environment.